From Necessity to Choice: A Study of Student Perceptions Toward Online Learning After the Pandemic - Elin, Lestariyanti; Dian, Tauhidah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Learning in the post-pandemic period has been permitted to resume offline. While some institutions continue to implement online learning, others have mandated a full return to offline instruction. This study aims to explore students' perceptions and preferences regarding the application of online learning during the post-pandemic period. The research employed a quantitative descriptive approach. The sample consisted of 72 biology education students from UIN Walisongo Semarang, selected through purposive sampling based on their online learning experiences during the pandemic. Data were collected using a Likert-scale questionnaire developed from the dimensions of perception and preference. The data were analyzed using t-tests and descriptive statistics presented as percentages, supplemented by qualitative descriptions. The results indicate that students' perceptions of online learning are influenced by factors such as internet connectivity, learning environment, and the selection of appropriate techniques and methods. Although students prefer offline learning, they still consider online learning as a viable alternative. Effective coordination among students, lecturers, parents, and institutions is essential to support the implementation of online learning in the post-COVID-19 era.